2018
DOI: 10.1021/acs.jpcc.8b06671
|View full text |Cite
|
Sign up to set email alerts
|

Dual Functions of Water in Stabilizing Metal-Pentazolate Hydrates [M(N5)2(H2O)4]·4H2O (M = Mn, Fe, Co, and Zn) High-Energy-Density Materials

Abstract: High-energy-density materials (HEDMs) containing the cyclopentazole anion (cyclo-N 5 ) are highly desirable due to the release of more energy and being environmentally more friendly than conventional HEDMs. However, the synthesis of stable cyclo-N 5 -containing HEDMs has been a challenge. In this study, quantum mechanical calculations were employed to elucidate the stability of [M(N 5 ) 2 (H 2 O) 4 ]•4H 2 O (M = Mn, Fe, Co, and Zn), one of the few recently reported cyclo-N 5 -contained HEDMs, under ambient con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Luo's study showed that water can improve the stability of Zn(N 5 ) 2, because the dissociation energy of [Zn(N 5 ) 2 (H 2 O) 4 ]·4H 2 O is higher than that of Zn(N 5 ) 2 . This study further reveals the stabilization mechanism of water, that is, the charge transfer and strong interactions between Zn(N 5 ) 2 and water make Zn(N 5 ) 2 more stable.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Luo's study showed that water can improve the stability of Zn(N 5 ) 2, because the dissociation energy of [Zn(N 5 ) 2 (H 2 O) 4 ]·4H 2 O is higher than that of Zn(N 5 ) 2 . This study further reveals the stabilization mechanism of water, that is, the charge transfer and strong interactions between Zn(N 5 ) 2 and water make Zn(N 5 ) 2 more stable.…”
Section: Resultsmentioning
confidence: 99%
“…In these compounds, [M(H 2 O) 4 (N 5 ) 2 ]·4H 2 O (M = Mn, Fe, Co, and Zn) are particularly interesting. They are all metal‐pentazolate hydrates, and Luo and coworkers have recently studied the role of water in these compounds …”
Section: Introductionmentioning
confidence: 99%
“…Almost all the pentazolate complexes are stabilized through hydrogen bonds by connecting with water or ammonia based on the experiments, such as Fe(H 2 O) 4 (N 5 ) 2 [4,21] . It should be noted that cyclo ‐N 5 − is the isoelectronic species of the high stable pentadienide cyclo ‐C 5 H 5 − , both containing a 5‐center‐6‐electron delocalized π bond.…”
Section: Introductionmentioning
confidence: 95%
“…(N 5 ) 6 (H 3 O) 3 (NH 4 ) 4 Cl is the first successfully synthesized complex containing cyclo ‐N 5 − with the decomposition temperature of 116.8 °C, which is a landmark achievement in this field [3,15,16] . Then a series of metal pentazolate complexes have been synthesized continuously, [17] such as [Na(H 2 O)(N 5 )] ⋅ 2H 2 O, M(H 2 O) 4 (N 5 ) 2 (M=Mn, Fe, Co and Zn) and [Mg(H 2 O) 6 (N 5 ) 2 ] ⋅ 4H 2 O [4,18–21] . Gong et al reported that the kinetic barriers of decomposition of M(N 5 ) 2 (M=Mg, Ca, Sr and Ba) are ranged from 23.4 to 25.5 kcal/mol, less than that of individual cyclo ‐N 5 − (27 kcal/mol) [8,22–23] .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation